PERANCANGAN APLIKASI PENGELOLAAN KOS BERBASIS WEB MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Gian Ramanda; Bagus Mulyawan; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The design of a web-based boarding house operational application with a User-Centered Design (UCD) approach aims to improve the efficiency and accuracy of operational management at Kos Mandiri. This application is designed to replace the manual recording system that has been used, which has the potential to cause data errors and hamper productivity. By applying the UCD approach, this application ensures that the features developed are in accordance with the needs of users, both residents and boarding house owners. The design of the application display, which has been outlined in the form of wireframes, is expected to provide convenience in managing room data, payments, and complaints, as well as improving user experience. This application is expected to be a more efficient, transparent, and accessible solution for better boarding house management in the future.